농업·농촌 녹색성장 정책수단의 우선순위 결정 : 계층분석과정(AHP)의 적용 - 김창길 (한국농촌경제연구원, 2013)
There are a lot of policy instruments of green growth which is defined as economic growth that creates new growth power and job opportunities while minimizing environmental pollution and greenhouse gases. Green growth policies in agriculture and rural districts are classified into six policies: climate policy, energy policy, policy for creation of green space, resource management policy, green industry policy, and green technology policy. This paper analyzes the priority of policy instruments of green growth using the analytic hierarchy process which determines priorities of policy programs by applying the criteria for policy evaluation based on survey of expertise. The result shows that efficiency is the most important policy evaluation criterion and so improving energy use efficiency, establishing an efficient R&D system and promoting bio-industry are very crucial policy measures.
Keywords: 녹색성장정책; 계층분석과정; 다기준 의사결정법; 정책우선순위; green growth policy; analytic hierarchy process; multi-criteria decision making; policy priorities